The Indian Educational TV: : Outreach, Perceptions and Preferences - Kumar, Abhay; Gupta, Deepty; Singh, Nidhi; Bhakuni, Monika; Vaishali; Arora, Komal; Khatri, Ruchi; Shukla, Abhay Kumar; Yadav, Kamlesh Kumar; Behera, Amarendra (Voices of Teachers and Teacher Educators, 2024)
This research paper is based on a dipstick survey aimed at understanding the role of educational television in improving access to educational opportunities for students living in remote areas in India. The study investigates the outreach of educational TV, with special focus on analysing the awareness of PM e Vidya DTH TV channels among students across geographical areas, gender and age groups. It further explores the role of educational TV during the COVID-19 pandemic and investigates perceptions towards educational TV, along with varying preferences for types of eContent among teachers, students and parents regarding its content. The data were collected from 13 states and two union territories, primarily involving responses from school-going children in rural and urban areas, as well as their teachers and parents. The study employed a descriptive survey research design and adopted a quantitative approach to analyse the data gathered through online survey questionnaires. It was found that educational TV programmes supported the educational needs of 89.7% students during COVID-19.Additionally, a significantly higher percentage of students (77.66%) compared to teachers (65.06%) agreed that eContent is beneficial for learning.